Studying The Myth Of Water In Ancient Iran And Its Relationship With Rain-Making Rituals - Goharpour, Hasan; Jalalkamali, Vahide (The Turkish Online Journal of Design Art and Communication, 2016)
Iran have always been conflicting with drought. As Dariush asks Ahura Mazda in his inscription in Takhte Jamshid to protect Iran from drought and lies. Creating myths is the first reaction of man’s mind at the face natural disasters, because the primary human were confused in understanding the causes of these occurrences, thus, their reaction were infused with fear and this fear has caused them to assume a metaphysical god for each phenomenon and seek shelter from him. As time flows, it becomes clearer that myths are a land’s valuable resources which can shed a light on the dark and unknown past. In the fables of creation, Water is one of the first things to be physically created and this is because of the significance of this life giving element. Thus, it is not far from expectation that the rain-making rituals and holding them during droughts have been always common in the ancient history of Iran.
Keywords: Myth; Water; Anahita; Rain-making ritual; Ancient Iran